2003
DOI: 10.1103/physreve.68.026409
|View full text |Cite
|
Sign up to set email alerts
|

Radiation from high-intensity ultrashort-laser-pulse and gas-jet magnetized plasma interaction

Abstract: Using a gas-jet flow, via the interaction between an ultrashort high-intensity laser pulse and plasma in the presence of a perpendicular external dc magnetic field, the short pulse radiation from a magnetized plasma wakefield has been observed. Different nozzles are used in order to generate different densities and gas profiles. The neutral density of the gas-jet flow measured with a Mach-Zehnder interferometer is found to be proportional to back pressure of the gas jet in the range of 1 to 8 atm. Strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…5 Properties of laser propagation in magnetized plasmas have been also studied widely, where most of the works are focused on self-generated high magnetic field or Cerenkov wake radiation. [6][7][8][9] Theoretical works for the case of Xmode 10,11 showed that RBS spectroscopic peak shifts from the incident laser's frequency by an amount of upper hybrid frequency x h and the scattering growth rate decreases as the magnetic field increases. However, there has been almost no experimental or simulation study on the effects of external magnetic field on RBS and RFS.…”
mentioning
confidence: 99%
“…5 Properties of laser propagation in magnetized plasmas have been also studied widely, where most of the works are focused on self-generated high magnetic field or Cerenkov wake radiation. [6][7][8][9] Theoretical works for the case of Xmode 10,11 showed that RBS spectroscopic peak shifts from the incident laser's frequency by an amount of upper hybrid frequency x h and the scattering growth rate decreases as the magnetic field increases. However, there has been almost no experimental or simulation study on the effects of external magnetic field on RBS and RFS.…”
mentioning
confidence: 99%
“…In this case, the generation of terahertz wave fields is related to the Vavilov-Cherenkov effect, because the velocity of the laser pulse exceeds the phase velocity of the slow extraordinary wave excited by the pulse. This problem was investigated in the cases of transverse propagation of laser pulse relative to the external magnetic field [23,62,220,247,249] and longitudinal (along the magnetic field) propagation of the laser pulse [109].…”
Section: Laser-plasma Acceleration Of Charged Particlesmentioning
confidence: 99%
“…Based on the report of Gupta et al [25], they did not have the effect of external magnetic field up to 20 MG in an underdense subrelativistic plasma and the effect is enhanced by increasing the magnetic field intensity up to 45 MG, where we have noticed an almost similar dependence of mentioned parameters to the magnetic field intensity in the present analytical work. Although some valuable experimental works are reported, the introduced analytical works did not properly explain the fundamental parameters of the magnetized plasma including electric and magnetic field oscillations or the derived equations being related to very special conditions [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%